Adapting to online education through project-based learning in a complex remote zone (Magallanes/Chile) - Vivar Vivar, Berta Marianela; Villarroel Ortega, Jorge Alejandro; Segura Sierpe, Yasna Pamela; Villarreal Cardenas, Claudio; Ojeda, Claudia (My University, 2021)
Faced with the health emergency caused by the SARS-CoV-2 virus, the Chilean government declared a state of catastrophe due to public calamity throughout Chilean territory. The University of Magallanes, since the beginning of the 2020 academic year, has started online classes. Accelerated changes have been motivated the development of theoretical and practical classes in laboratories for both the Construction Engineering faculty and students. Forcing them to adapt to this new form and to face the learning of engineering from their homes. The purpose of this research was to evaluate the learning process carried out during the academic period, as well as the effectiveness of its implementation in a virtual model of the design of the General Construction and Structural Analysis I courses. One of the ways to learn about the student's perception of the implementation of the virtual learning was through a final survey on both subjects, that evaluated the criteria of internet quality, satisfaction with the activity carried out, and the quality of the item. In the General Construction course, the laboratory was evaluated by asking the students to build a scale model of a house. This was carried out through collaborative work in a project which was evaluated by items through photographs uploaded to the cloud. The passing rate of the students was 90.9%. For the Structural Analysis I course, we used the teaching methodology called "Design Thinking". The assignment consists of making models with accessible materials in their home and of which the structural models differ between an inverted catenary and a suspension bridge. The evaluation was through a video with teacher feedback. The students passing rate was 72.7%. The evaluation of the process through the survey was considered positive by the students.
Keywords: assessment; construction engineering; online classes; project based learning